2012
DOI: 10.1097/sla.0b013e318265819c
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic Lobectomy Has Increasing Benefit in Patients With Poor Pulmonary Function

Abstract: Objective Using a national database, we asked whether video-assisted thoracoscopic surgery (VATS) lobectomy is beneficial in high-risk pulmonary patients. Background Single-institution series demonstrated benefit of VATS lobectomy over lobectomy via thoracotomy in poor pulmonary function patients [FEV1 (forced expiratory volume in 1 second) or DLCO (diffusion capacity of the lung to carbon monoxide) <60% predicted]. Methods The STS General Thoracic Database was queried for patients having undergone lobecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
160
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(173 citation statements)
references
References 35 publications
6
160
2
3
Order By: Relevance
“…It has become clear that VATS lobectomy has an advantage over thoracotomy in terms of morbidity, especially in patients with poor pulmonary function (14), and can be performed under sound oncological principles. VATS lobectomy has been demonstrated to have a lower incidence of arrhythmia, blood transfusion, renal failure, need for re-intubation, and shorter length of hospital stay and chest tube duration than open thoracotomy (8,15).…”
Section: Minimally Invasive Surgical Approachesmentioning
confidence: 99%
“…It has become clear that VATS lobectomy has an advantage over thoracotomy in terms of morbidity, especially in patients with poor pulmonary function (14), and can be performed under sound oncological principles. VATS lobectomy has been demonstrated to have a lower incidence of arrhythmia, blood transfusion, renal failure, need for re-intubation, and shorter length of hospital stay and chest tube duration than open thoracotomy (8,15).…”
Section: Minimally Invasive Surgical Approachesmentioning
confidence: 99%
“…Although a large number of patients could not be offered surgery due to age or comorbidities in the past, the progress in thoracic anaesthesia, perioperative medicine and surgical techniques now allow octogenarians and patients with significant cardiopulmonary comorbidities to undergo lung resections routinely [31]. The estimation of in-hospital death and complications is of paramount importance to decide whether a patient should be offered surgery or not and to inform the patient in the best possible way.…”
Section: Assessment Of the Risk For Surgerymentioning
confidence: 99%
“…Therefore, lung resection should be considered even in patients with very poor pulmonary function, when the tumour is situated in the most emphysematous lobe [19]. Recently, an analysis of the STS database showed that thoracotomy had a markedly negative impact on complications compared with VATS lobectomy in patients with FEV1 ,60% predicted or DLCO ,60% predicted [31].…”
Section: Surgery In Patients With Impaired Pulmonary Functionmentioning
confidence: 99%
“…Video-assisted thoracic surgery (VATS), a minimally i n v a s i v e a p p r o a c h w i t h s e v e r a l a d v a n t a g e s o v e r thoracotomy for early stage lung cancer (1)(2)(3)(4)(5), its use is limited because of rigid instruments and poor 2-dimensional visualization. With technological innovations, robotic surgical systems appears to have several theoretical advantages over traditional VATS, including 3-dimensional field of view, improved greater dexterity due to more degrees of movement freedom of robotic arms and great comfort for the surgeon (6,7).…”
Section: Introductionmentioning
confidence: 99%